(untitled) (LEARNing Landscapes, 2009)
Two authors from different disciplines share their views on meeting both the curriculum set forth by the institution and honouring the meaning that students make of their own learning. Believing in the importance of learning that reaches beyond that which is taught, the real curriculum, the authors discuss the challenge of finding a balance between assessing required course content and honouring individual growth in our assessment-laden society.